Levels of Detoxifying Enzyme (General Esterases and GST) in the Worker and the Soldier Castes of Odontotermes obesus (R.): A Possible Adaptation to Tolerate Exposure to Pesticides - Biswa, Ritesh; Mukhopadhyay, Ananda (International Journal of Bio-resource and Stress Management, 2013)
North Bengal Tea Plantations produces about 24% of Indian tea. Using synthetic pesticides to an extent of 5.799 to 9.793 Kg l-1ha-1yr-1 has resulted in selection of more tolerant pest populations. Among the tea pests, termite occupies a distinct niche by attacking tea plants from under soil or at collar region of a bush. Termites are important subterranean pests in tea where they limit the establishment of newly planted young tea and reduce the mature tea by attacking their frame and killing bushes. Termites are social insects with a highly elaborate system of labor division. Based on the labour division in the colony, it has been observed that worker caste is more exposed to the toxic xenobiotic or pesticide residues of soil and organic matter of tea plantations, than any other castes including soldier castes of a colony. A comparative study of detoxifying enzymes General Esterases (GE) and Glutathione S-Transferase (GST) between worker and soldier castes of Odontotermes obesus, a major subterranean pest of tea, was conducted. Quantitative analysis of GE showed a 3.46 folds higher expression in worker termites compared to that of the soldiers. GST was also 2.45 folds more in workers than in soldiers. The differential feeding and foraging habits of the workers of O. obesus may explain the observed differences with the soldiers in these detoxifying enzymes. As the workers search for food, digest them and also feed the other castes their contact and exposure to pesticide residue in soil and organic debris is much which possibly explains the more level of detoxifying enzymes in them for a greater tolerance to these xenobiotics for survival in the pesticide changed soil system of tea plantations than soldier or reproductive castes.